Protecting Their Daughters with Knowledge: Understanding Refugee Parental Consent for a U.S.-Based Teen Sexual Health Program. Issue 4 (2nd October 2022) - Morrison-Beedy, Dianne; Ewart, Abigail; Ross, Samiha; Wegener, Rachel; Spitz, Alison
Abstract: Due to limited knowledge and exposure to sexual health information, refugee adolescent girls need health education programming and research studies that oftentimes require parental consent. We sought to understand the parental consent decision-making process of thirteen refugee parents from eight different countries who consented for their 15–17-year-old daughters to participate in a sexual health promotion program. Interviews with eight mothers and five fathers provided insight into motivations and concerns driving their decision, as well as barriers and facilitators for obtaining consent. In-depth qualitative thematic analysis revealed five predominant themes: (1) Protecting our daughters with knowledge ; (2) A different country, a different approach to protection ; (3) Consent and understanding can be different ; (4) Parents cannot do it all ; and (5) My daughter gained a voice. These findings are useful for developing consent protocols and tailored programming to meet the needs of this understudied population.